CONTENT ANALYSIS ON TWO ENGLISH TEXTBOOKS FOR THE EIGHTH GRADER OF JUNIOR HIGH SCHOOL - Ary Setya Budhi Ningrum; Uum Midah Lestari; Nurul Retno Murti (Widya Mandala Surabaya Catholic University, 2023)
This paper reports a study that analyzed the content of two English textbooks used in junior high school in Indonesia. The two textbooks are officially published by Indonesia's Ministry of Culture and Education. The first is